If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q = 2(q + -19) Reorder the terms: q = 2(-19 + q) q = (-19 * 2 + q * 2) q = (-38 + 2q) Solving q = -38 + 2q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-2q' to each side of the equation. q + -2q = -38 + 2q + -2q Combine like terms: q + -2q = -1q -1q = -38 + 2q + -2q Combine like terms: 2q + -2q = 0 -1q = -38 + 0 -1q = -38 Divide each side by '-1'. q = 38 Simplifying q = 38
| 1/3x=12.85 | | p=2(p-26) | | 18x-24=36-2x | | 10=2/5xn | | q=2(q-41) | | 10=2/5n | | 6m^2-m-7=0 | | X-v=-27+48 | | (13+-2x)4+-2x=16 | | z=2(z-12) | | s+11=2s | | z=2(z-32) | | 16x^2-9=91 | | 2x+50=3y | | (8-4x)3+2x=-108 | | z-7=2z-31 | | (w-2)2= | | 4(3)+3(y)=6 | | 9(12n-6)=15(7n) | | 4(3)+3y=6 | | 2x^2-4x=19 | | (7-3x)3-7x=1 | | x*a=287 | | (2+3x)2+-5x=13 | | a*b=287 | | w=2w-49 | | 4(5x+1)-2(3x-4)=12x+36 | | w=w-40 | | Cot^2(3x)=1 | | 3x^5=-3 | | 49w^2+35w+6=0 | | X=8/3x-16 |